Pengenalan Konsep Fisioterapi Wellness dan Pemeriksaan Kesehatan Dasar di SMAN 6 Cimahi - Qudus, Abdul; Firmansyah Sumantri, Agung; Halomoan, Roni; Thesalonika, Lona; Sudrajat, Agus; Kusdiantini, Andini; Trimastuti, Wahyu; Gunawan, Ramdhan; Mecca Sufyana, Candra (PADMA, 2022)
The student period is a critical time for forming lifestyle patterns. Wellness physiotherapy emphasizes prevention, health promotion, and the formation of safe physical activity habits.The purpose of introducing the concept of wellness physiotherapy and conducting basic health checks for students at SMAN 6 Cimahi is to increase health awareness and detect early risk factors.The PKM activity took the form of group education and basic health screening (pre-activity questionnaires such as PAR-Q+, blood pressure measurement, body mass index, resting heart rate, sit-and-reach flexibility, and screening for health problems). The PKM activity took the form of group education and health screening examinations (pre-activity questionnairessuch as PAR-Q+, blood pressure measurements, body mass index, resting heart rate, sit-and-reach flexibility, and simple functional fitness measurements). The results were reported descriptively, and clinical follow-up was recommendedwhen necessary. Results from 120 participating students showed that 18% exhibited signs of high blood pressure/other risk factors requiring follow-up, 32%did not meet physical activity recommendations, and >85% reported increasedknowledge after the session. This program is effective as an initial intervention toincrease student health awareness and detect health issues requiringreferral.